Efficacy and safety of transesophageal ultrasound-guided patent foramen ovale closure for migraine in adolescents - Mi, Zeyu; He, Gang; Li, Chao; Yang, Deyu; Liu, Xue; Zhao, Libo; Gao, Hongli; Li, Xing; Zhou, Xiaogang (Frontiers in Pediatrics, 2023)
Abstract Objective: This retrospective analysis aims to assess the efficacy of transesophageal ultrasound-guided patent foramen ovale (PFO) closure in treating migraine in adolescents and compare the therapeutic outcomes of PFO closure for migraine with and without aura. Methods: We conducted a retrospective analysis of 86 cases of adolescents (12–20 years old) who underwent PFO closure for migraine at our institution over the past 3 years. The efficacy was evaluated using the visual analogue scale (VAS), headache impact test (HIT)-6, and pediatric migraine disability assessment (PedMIDAS) scores, as well as by assessing the monthly frequency of migraine attacks, duration of each attack, and overall migraine burden. The patients were divided into two groups: an aura group (55 cases) and a non-aura group (31 cases) to investigate difference in therapeutic efficacy between the groups. The effect of residual shunt on migraine burden was assessed. Results: Among the 86 patients, 46 (54%) experienced complete remission of migraine, while 71 (83%) achieved a >50% reduction in migraine burden during the one-year follow-up period. Patients in the aura group showed more significant improvements in VAS, HIT-6, and PedMIDAS scores, as well as in monthly migraine attack frequency, duration of each attack, and overall migraine burden, than patients in the non-aura group. Moreover, patients with residual shunt did not exhibit statistically significant differences in therapeutic efficacy compared to patients with complete closure. Conclusion: PFO closure can effectively alleviate migraine symptoms in adolescents with migraine with concomitant PFO. The therapeutic efficacy is particularly pronounced for migraine with aura. Furthermore, minor levels of residual shunt have no effect on the improvement in migraine symptoms.